2008
DOI: 10.1152/ajpheart.01086.2007
|View full text |Cite
|
Sign up to set email alerts
|

Alternans of cardiac calcium cycling in a cluster of ryanodine receptors: a simulation study

Abstract: Mechanical alternans in cardiac muscle is associated with intracellular Ca 2ϩ alternans. Mechanisms underlying intracellular Ca 2ϩ alternans are unclear. In previous experimental studies, we produced alternans of systolic Ca 2ϩ under voltage clamp, either by partially inhibiting the Ca 2ϩ release mechanism, or by applying small depolarizing pulses. In each case, alternans relied on propagating waves of Ca 2ϩ release. The aim of this study is to investigate by computer modeling how alternans of systolic Ca 2ϩ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 42 publications
(45 reference statements)
4
36
0
Order By: Relevance
“…In particular, we showed that when the system is paced close to the Ca wave onset then the beat-to-beat response of the system displays Ca transient alternans. This finding is consistent with experimental and theoretical studies [19,21,22] showing that large amplitude alternans of the Ca transient during alternans corresponds to a release sequence where Ca waves are observed on the large beat, but not on the small. This nonlinear response is due to the steep release load relationship that is observed near the wave onset transition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, we showed that when the system is paced close to the Ca wave onset then the beat-to-beat response of the system displays Ca transient alternans. This finding is consistent with experimental and theoretical studies [19,21,22] showing that large amplitude alternans of the Ca transient during alternans corresponds to a release sequence where Ca waves are observed on the large beat, but not on the small. This nonlinear response is due to the steep release load relationship that is observed near the wave onset transition.…”
Section: Discussionsupporting
confidence: 92%
“…Fluorescence imaging under these conditions demonstrated that waves propagate only on alternate beats, indicating that wave propagation played a key role in the instability to alternans. Using a computational model Tao et al [21] showed that indeed Ca alternans can be caused by wave propagation which occurred at alternate beats. In a later study Li et al [22] showed that spatial heterogeneity of the Ca signaling system made atrial cells more prone to Ca waves, which led to a steep SR load dependence of release which caused alternans.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of Ca i -driven alternans have been analyzed in many previous studies (11,37,44,46). The exact dynamical mechanism by which fibroblast-myocyte coupling promoting Ca i alternans is not completely clear, but the early I to -like phase of I gap appears to play a key role, since increasing I to in the rabbit ventricular model had the same dynamical effects (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…This mechanism requires that Ca DSRL alternate concomitantly with SR Ca release, but the refractoriness of SR Ca release is not explicitly required. Subsequent mathematical analyses and simulation studies either potentiated this theory (30,45,57,64,69,71) (41), and the importance of refractoriness in Ca alternans has been demonstrated in later studies (32,58). Therefore, the above experimental studies raise the issue of the roles of SR Ca and refractoriness of SR Ca release in the genesis of Ca alternans.…”
mentioning
confidence: 96%
“…This mechanism requires that Ca DSRL alternate concomitantly with SR Ca release, but the refractoriness of SR Ca release is not explicitly required. Subsequent mathematical analyses and simulation studies either potentiated this theory (30,45,57,64,69,71) or used it to study subcellular Ca alternans dynamics (21,56). On the other hand, experimental studies in rabbit ventricular myocytes by Picht et al (41) and in cat atrial myocytes by Huser et al (25) showed that Ca alternans can occur without Ca DSRL alternans.…”
mentioning
confidence: 99%